2022
DOI: 10.1021/acs.jmedchem.2c01000
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Biological Characterization of PRMT5:MEP50 Protein–Protein Interaction Inhibitors

Abstract: Protein arginine methyltransferase 5 (PRMT5) is a master epigenetic regulator and an extensively validated therapeutic target in multiple cancers. Notably, PRMT5 is the only PRMT that requires an obligate cofactor, methylosome protein 50 (MEP50), to function. We developed compound 17, a novel small-molecule PRMT5:MEP50 protein−protein interaction (PPI) inhibitor, after initial virtual screen hit identification and analogue refinement. Molecular docking indicated that compound 17 targets PRMT5:MEP50 PPI by disp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…In contrast, to discover inhibitors of PRMT5-substrate adaptor PPIs, Asberry and co-workers focused on developing small-molecule inhibitors of the PRMT5:MEP50 interaction. 87 A virtual screening of over 30 million molecules from the ZINC database identified compound 39 (Figure 13A) as a hit in combination with a bimolecular fluorescence complementation (BiFC)-based screen in cells, which showed that 41% of the BiFC efficiency was inhibited after treatment with compound 39 at 250 nM. Molecular docking of compound 39 into the TIM barrel of PRMT5 indicated that it occupies the MEP50-Trp54 binding pocket (Figure 13B).…”
Section: Inhibitors Targeting Prmt5−adaptor Protein Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, to discover inhibitors of PRMT5-substrate adaptor PPIs, Asberry and co-workers focused on developing small-molecule inhibitors of the PRMT5:MEP50 interaction. 87 A virtual screening of over 30 million molecules from the ZINC database identified compound 39 (Figure 13A) as a hit in combination with a bimolecular fluorescence complementation (BiFC)-based screen in cells, which showed that 41% of the BiFC efficiency was inhibited after treatment with compound 39 at 250 nM. Molecular docking of compound 39 into the TIM barrel of PRMT5 indicated that it occupies the MEP50-Trp54 binding pocket (Figure 13B).…”
Section: Inhibitors Targeting Prmt5−adaptor Protein Interactionmentioning
confidence: 99%
“…According to their different binding pockets, the first-generation PRMT5 inhibitors can be classified into two types. One type is designed by targeting the PRMT5 SAM binding pocket, while the other type targets the substrate binding pocket. , In addition, novel strategies have been explored to target PRMT5, resulting in the discovery of PRMT5 covalent inhibitors, allosteric inhibitors, targeted degraders, PRMT5-adapter protein–protein interaction (PPI) inhibitors and synthetic lethal inhibitors . Such diverse PRMT5 inhibitors with novel mechanisms of action (MOA) provide alternative therapeutic options compared with those of first-generation PRMT5 inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of this was recently demonstrated by Asberry and colleagues, who reported the first biologically active inhibitor of PPI between PRMT5 and MEP50, highlighting the strong community interest in targeting these challenging PRMT5 interactions with the adaptor proteins. 15 We, and independently the Sellers group, recently reported the identification and characterization of a novel PRMT5 binding motif (PBM) with the consensus sequence GQF[D/ E]DA[E/D] found in the adaptor proteins pICln, RioK1, and COPR5. 5,6 Methylation of 25 PRMT5 substrates is dependent on the interaction between the PBM and the PBM binding groove located on the TIM barrel of PRMT5.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Being able to selectively modulate one of the PRMT5 PPIs would allow one to inhibit the methylation of only a subset of its targets. The feasibility of this was recently demonstrated by Asberry and colleagues, who reported the first biologically active inhibitor of PPI between PRMT5 and MEP50, highlighting the strong community interest in targeting these challenging PRMT5 interactions with the adaptor proteins …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation